Assessment of documentation on current patient’s medical records at Accident and Emergency Hospital of Sulaimani-Iraq - Qader, Delan Jamal; Faraj, Faruk Hassan (Kurdistan Journal of Applied Research, 2019)
The patient record is an essential patient data were the nursing documentation part is fundamental. .Competent nursing care is based on correct and complete records, and keeping record is an essential skill that needs to be developed by each and every health staff. The present study was conducted in order to assess the documentation on current medical patient’s records in the Accident and Emergency Hospital/Sulaimani city. A quantitative descriptive design. Research was accomplished, based on retrospective data made available by the Accident and Emergency Hospital. Non-probability (purposive sample) of 201 patient files were selected from 1,194 patient files during 6 months between Jun to December 2016.The present study showed that the face sheet was completely recorded about %95 which means satisfactory, other items which were recorded by physician such as chief complaint and history of present illness, radiology, laboratory, medication intervention report, consent forms, physical examination, and consultant report were unsatisfactorily recorded. Last items which were recorded by the nurse who working in Accident and Emergency Hospital medication and administration record and a graphic sheet of vital signs were unsatisfactorily recorded. Deficiency in documentation system and most of the provided medical and nursing care remains undocumented given numerous deficiencies in the documentation system. It is recommended the components of the nursing record tool can be utilized once a paperless system is implemented as planned in the hospital.